Impact of the grazing ban on the forest soil nutrient dynamics in the Sikkim Himalaya, India - Ghanashyam Sharma; Bharat K. Pradhan; Prakash Chhetri (Academia Biology)
With more than two decades of livestock grazing prohibition in Sikkim, understanding its impact on forest ecosystem, particularly soil nutrient dynamics, is crucial. Soil nutrient analyses were conducted on samples from four study sites at two depths (0–15 cm and 15–30 cm) during rainy and winter seasons. The treatments were (1) current grazing forests (CGFs; areas where herders graze their animals), (2) old grazed forests (OGFs; grazing was prevalent before the ban on grazing), (3) ungrazed forests (UGFs; not impacted by livestock grazing), and (4) abandoned Kharkas (AKs; open-grazing pastures). Mean soil total nitrogen content in CGF (0.45%) > OGF (0.41%) > UGF (0.37%) > AK (0.34%) showed significant differences (p < 0.05). Similarly, the mean available phosphorus content in CGF (0.12%) and OGF (0.009%) was significantly (p < 0.05) higher than UGF (0.007%) and AK (0.006%). Likewise, the mean soil total phosphorus in CGF (108.21 mg 100 gm–1) > OGF (94.75 mg 100 gm–1) > UGF (89.02 mg 100 gm–1) > AK (83.24 mg 100 gm–1) revealed significant (p < 0.05) variation. Mean soil organic carbon and soil organic matter in CGF (3.86%, 6.64%) > OGF (3.76%, 6.47%) > UGF (3.56%, 6.13%) > AK (3.34%, 5.75%) and carbon:nitrogen ratio in CGF (8.61) < OGF (9.19) < UGF (9.53) < AK (9.97) showed significant differences (p < 0.05). Our results confirm that the management of controlled, regulated, and rotational grazing is beneficial for improving the forest ecosystem health in terms of soil nutrient availability.